Telemedicine in Postoperative Monitoring After Oral Surgery: Clinical Outcomes, Patient Satisfaction, and Health Equity Implications - Stenzel, Paweł; Niewola, Karolina; Arciszewski, Kamil; Hariasz, Natalia; Orda, Karolina; Walczak, Dominika; Szumiło, Jakub; Kasperska, Klaudia; Markiv, Mariana; Słowik, Michał (Journal of Education, Health and Sport, 2026)
Background. Telemedicine has become an important component of postoperative care in oral and maxillofacial surgery, especially after the COVID-19-driven expansion of remote clinical services. Current evidence suggests potential benefits in safety, convenience, and resource utilization, but implementation challenges remain. Aim. To synthesize current evidence on telemedicine in postoperative monitoring after oral surgery, with emphasis on clinical outcomes, patient satisfaction, operational efficiency, and health equity implications. Material and methods. A narrative literature review was conducted using PubMed/MEDLINE, Scopus, and Google Scholar, focusing primarily on studies published between 2006 and 2026. Eligible studies evaluated telemedicine-based postoperative follow-up in oral and maxillofacial surgery and reported outcomes related to clinical safety, complication detection, patient-reported experience, access, or economic impact. Results. Across low-risk oral surgery pathways, remote follow-up showed outcomes comparable to in-person care for symptom monitoring and complication screening. Patient satisfaction was consistently high, with many patients preferring telemedicine after direct use. Telemedicine reduced travel burden, waiting time, and patient-side costs, and supported more efficient allocation of clinical resources. At the same time, limitations included restricted physical examination and potential inequities related to digital literacy and connectivity. Conclusions. Telemedicine is a safe and effective adjunct for postoperative monitoring in selected oral surgery patients and should be integrated within hybrid, risk-stratified care models. Wider implementation requires clear escalation protocols, inclusive digital design, and supportive policy frameworks to ensure quality and equitable access.